2010
DOI: 10.1038/nrg2776
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing and evolution: diversification, exon definition and function

Abstract: Over the past decade, it has been shown that alternative splicing (AS) is a major mechanism for the enhancement of transcriptome and proteome diversity, particularly in mammals. Splicing can be found in species from bacteria to humans, but its prevalence and characteristics vary considerably. Evolutionary studies are helping to address questions that are fundamental to understanding this important process: how and when did AS evolve? Which AS events are functional? What are the evolutionary forces that shaped,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
839
3
7

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 942 publications
(866 citation statements)
references
References 121 publications
17
839
3
7
Order By: Relevance
“…This difference is likely the consequence of the relative contribution of gene duplication and alternative splicing to genome expansion in each lineage. Zebrafish have very high rates of gene duplication (Lu et al 2012) and display very low levels of alternative splicing (Lu et al 2010), while the inverse is true for humans (Shoja and Zhang 2006;Keren et al 2010). Therefore, it is not surprising that the effects of subfunctionalization will be amplified in a genomic background replete with alternative splicing yet relatively free of duplicate genes, as is the case with the human genome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference is likely the consequence of the relative contribution of gene duplication and alternative splicing to genome expansion in each lineage. Zebrafish have very high rates of gene duplication (Lu et al 2012) and display very low levels of alternative splicing (Lu et al 2010), while the inverse is true for humans (Shoja and Zhang 2006;Keren et al 2010). Therefore, it is not surprising that the effects of subfunctionalization will be amplified in a genomic background replete with alternative splicing yet relatively free of duplicate genes, as is the case with the human genome.…”
Section: Discussionmentioning
confidence: 99%
“…There are several types of alternative splicing events, including cassette exons, alternative 5 ′ and 3 ′ splice sites, mutually exclusive exons, and intron retention, with cassette exons being the most common in vertebrates. Interestingly, rates of alternative splicing correlate with organismal complexity, and it is alternative splicing that bridges the gap between the ∼22,000 genes within the human genome and the more than 100,000 unique proteins that the human genome codes for (Keren et al 2010). Given that both alternative splicing and gene duplication increase proteomic diversity, it is not surprising that several investigators have hypothesized that the two processes may be evolutionarily related.…”
mentioning
confidence: 99%
“…Two models explain the mechanism of exon and intron selection: intron definition and exon definition (Keren et al 2010). Placing the basal splicing machinery across introns is regarded as the ancient mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…3B,C). A specific set of histone modifications (including H2Bub1) may cause a well-defined ''exonic nucleosome'' during transcription elongation (Keren et al 2010). The more frequent occurrence of exon skipping in highly expressed genes (Fig.…”
Section: Specific H2bub1 Properties In Mammals Are Associated With Exmentioning
confidence: 99%
“…It is reported that this phenomenon take place in more than 90 % of the multiexons of H. sapiens [68]. Based on different splicing patterns, AS events can be categorized into several types: exon skipping, intron retention, mutually exclusive exon, alternative 5′ splice sites, alternative 3′ splice sites, alternative promoters, and alternative poly-A sites [69]. The process of alternative splicing is carried out by spliceosome and regulated through trans-acting factors and cis-acting sites [70].…”
Section: Alternative Splicing Of the P2x Genes In Vertebratementioning
confidence: 99%